31. RESULT OF PULSE CORTICOSTEROID AND PLASMAPHERESIS IN TREATMENT OF RAPIDLY PROGRESSIVE GLOMERULONEPHRITIS IN THE ELDERLY: CASE REPORT (Vietnam Journal of Community Medicine, 2024)
Rapidly progressive glomerulonephritis is a rare disease, especially in the elderly, that is a medical emergency in nephrology requiring prompt diagnosis and treatment to rescue the renal function.Objectives: to evaluate the results of the therapy of pulse corticosteroids and plasmapheresis in a case.Patients: male, 69 years old. The reason for admission was edema of the lower extremities. The initial diagnosis was nephrotic syndrome – acute kidney injury. Laboratory result confirmed the diagnosis of rapidly progressive glomerulonephritis. The patient was treated with pulse corticosteroids and plasmapheresis.Method: case reportResults: Renal biopsy was performed to conclude the pauci-immune crescentic glomerulonephritis. The ANCA tests were negative. The kidney function was recovered rapidly after 3 times of plasma exchange and discharged from the hospital after completing 10 courses of plasmapheresis.Conclusion: Prompt and aggressive treatment with pulse corticosteroids and plasmapheresis attained good results that rescued the patient and kidney function recovered completely.
Keywords: Rapidly progressive glomerulonephritis; pauci-immune crescentic glomerulonephritis; pulse corticosteroids; plasmapheresis